Hubungan Pola Asuh Orangtua Dengan Perkembangan Bahasa Anak Prasekolah Puskesmas Pegajahan Kec. Pegajahan Kab. Serdang Bedagai Tahun 2023 - Ayudiah Astuti; Isyos Sari Sembiring; Nita Indrayani; Nuriani Nuriani; Jumining Jumining; Ratna Metasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
BACKGROUND Children require special attention as the nation's next generation who will become valuable assets for future development, so that quality human resources can be formed. The first five years of human life greatly influence a child's growth and development for the next stage, especially for physical growth and intelligence. One of the factors that influences the child's growth process is nutritional status which determines success in improving the quality of human resources (Nurrizka and Saputra, 2015). The main causes of death in the group of children under five (12-59 months) were diarrhea at 10.3% and pneumonia at 9.4%. Other causes of death include dengue fever, congenital heart defects, drowning, injuries, accidents, other congenital disorders, COVID-19, parasitic infections and other causes. (Indonesia Health Profile, 2021). Undernutrition or overnutrition (malnutrition) will happen if food consumption patterns are wrong (Oemar, Novita, 2015). In 2017, 22.2% or around 150.8 million children under five in the world experienced malnutrition. However, this figure has decreased compared to data in 2000, namely 32.6%. In 2017, more than half of children under five experiencing malnutrition in the world came from Asia (55%) while more than a third (39%) lived in Africa. (Indonesian Ministry of Health, 2019). OBJECTIVE To analyze the pattern of nutritional intake on children's growth at the Pegajahan Community Health Center, Pegajahan District, Serdang Bedagai District in 2023. METHOD chi square test p value < 0.05 means H0 is rejected and Ha is accepted, the statistical test results show a significant relationship. RESULTS: There is a significant relationship between nutritional intake patterns and child growth, showing that the majority of respondents with good nutritional intake patterns have children with normal growth, namely 14 (77.8%). From the results of the chi-square test, it was found that the p value was 0.001 or less than 0.05, meaning that Ho was rejected and Ha was accepted that Nutritional Parenting Patterns on Child Growth at the Pegajahan Community Health Center, Pegajahan District, Serdang Bedagai District in 2023